ANALISIS IMPLEMENTASI MOTIVASI KERJA KARYAWAN - Zidane, Muhammad Yasser; Rofiaty, Rofiaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to analyze the implementation of employee’s work motivation at Bank Sinarmas Syariah in Malang. This research uses theories related to human resource management and motivation in human resource. The research object is the Islamic Business Unit of PT Bank Sinarmas in the branch office of Malang. This qualitative descriptive study uses the phenomenological approach. The primary data was harvested through interviews, observations, and documentation, which was analyzed using Moustaka’s data analysis theory. This model consists of data reduction, data elimination, data bracketing, data thematization, and data synthesis. Source triangulation and theoretical triangulation were used to validate the data. This study finds that the bank has used various forms and processes to implement the work motivation of its employees and that those forms and processes have been in line with theories related to work motivation as presented by experts.